Frederic Remington: Kansas Days - Jessie Perry Stratford; Lawrence Klintworth (Symphony in the Flint Hills, 2014)
In April of 1883 a young Frederic Remington bought a 160-acre sheep ranch in Butler County near the tiny settlement of Plum Grove, close to today’s Whitewater. This is a short story on the famous artist, Frederic Remington.
Keywords: Frederic Remington; Kansas; bonfire; Plum Grove Grade School; artist; drawings; sketches